Corporate Communication Summer Internship at Eureka Forbes Limited - Sinha, Harsh (ATLAS SkillTech University, 2024)
Corporate communication is an essential component of modern corporate operations, helping to shape an organization's perception, enabling productive cooperation, and cultivating deep connections with stakeholders on a worldwide scale. In order to transmit messages and support the company's beliefs, goals, and objectives, this form of communication uses a variety of mediums and tactics for both internal and external contacts. The dynamics of corporate communication have changed in an increasingly interconnected world, calling for a deeper comprehension and deliberate approach to engage a variety of audiences across various countries and cultures.
Project Report on Corporate Communication Summer Internship at Eureka Forbes Limited (2022-24) Under the Guidance of Prof. Tapish Panwar
Keywords: corporate operations; Corporate communication; productive cooperation; deep connections